Determination of Dividends and Their Implications for Share Prices in Property and Real Estate Companies in 2016-2020 - Aziz, Yanelsis Nurmala; Elfiswandi, Elfiswandi; Yulasmi, Yulasmi (Lembaga Penelitian dan Pengabdian Kepada Masyarakat Universitas Putra Indonesia YPTK, 2023)
After conducting a simple study of 41 property and real estate companies listed on the Indonesia Stock Exchange in Indonesia for five years (2016-020), the results of the description of the analysis of the effect of company size on financial performance and inflation on stock prices by dividend policy as an intervening variable, the data processing application used is SPSS.25 Based on research it is known that: (1) The variable company size and finacial performance partially has no positive and significant effect on dividend policy (2) The inflation variable partially has a positive and significant effect on dividend policy (3) The variable company size and financial performance partially has no positive and significant effect on stock prices (4) The inflation variable partially has a positive and significant effect on stock prices (5) The dividend policy variable partially has no positive and insignificant effect on stock prices (6) The dividend policy variable is unable to mediate the relationship between company size and share prices (7) The dividend policy variable is able to mediate the relationship between financial performance and share prices (8) The dividend policy variable is unable to mediate the relationship between inflation and share prices.